Women's Rights - Janovicek, Nancy (Labour / Le Travail, 2009)
The article reviews the book, "Women's Rights," by Geraldine Terry.
Keywords: BOOKS -- Reviews; Book reviews; Business And Economics--Labor And Industrial Relations; History--History of North And South America; Nonfiction; POVERTY; TERRY, Geraldine; WOMEN'S Rights (Book); Women's rights; Womens rights movement